ANALYSIS OF CIRCULATION WIDE EFFECT ON PERIPERSONAL SPACE FOR PREGNANT MOTHERS IN RETAIL STORE, Case Study : Mothercare Bandung. - Imtihan Hanom; Rizka Rachmawati; Tri Gustina Napitupulu; Thiflani Nurfauziyyah Ramadhanti (Ide dan Dialog Desain Indonesia (Idealog), 2020)
In the development of the retail business, one of the things that can add value is to pay attention to the interior design. The interior design of a retail store must be tailored to its users regarding the activities and activities in it. The focus of this research is to analyze users, especially pregnant women visitors, due to the expansion of the personal space of pregnant women so that it is different from other general visitors. With the expansion of the personal space of pregnant women, a behavior emerges, namely always keeping a distance so that other people do not easily touch or nudge the pregnant woman's stomach. This research specifically examines the store interior of the Mothercare brand, which is a retail store that provides all the special needs of pregnant women, babies and children. The choice of the brand is because Mothercare is the number one global retailer in the market for pregnant women, babies and children. This research focuses on the corridor of the display section of baby products and pregnant women. This is because the dimensions of the corridor width are not in accordance with human standards in general, especially for visitors to pregnant women who have expanded personal space. This study used a descriptive qualitative method by conducting studies through interviews, observation and distributing questionnaires to third trimester pregnant women respondents with a history of pregnancy for their first child. From the research results, it was found that the width dimension of circulation can significantly affect the personal space of pregnant women which results in perceptions and attitudes.Keyword : Interior Desing, Pregnancy Women, Personal Space, Retail Store, Mothercare